Histological investigation of a 10% metronidazole and 2% lidocaine dressing on wound healing in rats. - Rodrigues, T. S.; Poi, Wilson Roberto [UNESP]; Barioni, Sônia Regina Panzarini [UNESP]; Bezerra, C. S.; Silva, J. L. (My University, 2006)
AIM: Alveolitis is considered a disturbance of the alveolar healing process that is characterized by blood clot disintegration, alveolar wall infection and extreme pain. Several substances have been investigated to improve healing and guarantee postoperative comfort to patients. The aim of this study was to evaluate, microscopically, in rats, the healing process in non-infected tooth sockets, after application of a 10% metronidazole and 2% lidocaine dressing, using lanolin as vehicle and mint as flavoring. METHODS: Forty-five rats (Rattus norvegicus albinus, Wistar) had their right incisor extracted and were randomly assigned to 3 groups (n=15): Group I (control): the sockets were filled with blood clot; Group II: application of adrenaline solution at 1:1 000 with an absorbent paper point during 1 min plus filling of the socket with a 10% metronidazole and 2% lidocaine dressing, with lanolin as vehicle, and mint as flavoring; Group III: filling of the socket with the 10% metronidazole and 2% lidocaine dressing, with lanolin as vehicle and mint as flavoring. After 6, 15 and 28 days postoperatively, 5 animals per group were euthanized with an injectable anesthetic overdose. Histological and statistical analyses were performed. RESULTS: The results showed that the 10% metronidazole and 2% lidocaine dressing with lanolin as vehicle and mint as flavoring yielded similar response as that of the normal repair group and may be used to prevent the onset of alveolitis in those cases in which any predisposing factor is present. CONCLUSIONS: The use of this dressing has shown a good postoperative patient's comfort and does not cause a significant delay in the alveolar healing process.
Keywords: lidocaine; metronidazole; animal; drug combination; drug effect; evaluation; histology; male; periodontic device; physiology; rat; tooth socket; Wistar rat; wound healing; Animals; Drug Therapy, Combination; Lidocaine; Male; Metronidazole; Periodontal Dressings; Rats; Rats, Wistar; Tooth Socket; Wound Healing